Inter-story seismic isolation for high-rise buildings. (15th January 2023) - Forcellini, Davide; Kalfas, Konstantinos N.
Abstract: Inter-story seismic isolation has become a valuable solution for high-rise buildings to effectively separate the various parts having several functions, and thus different seismic performance requirements, with the main advantage being the interruption of the flux of energy between the upper and lower stories. The isolation layers that are introduced at various heights of the buildings may filter the inertial forces transmitted to the superstructure and improve the seismic behavior of the whole system. This paper studies a 20-floor building and several inter-story configurations where the isolation layer is located at several heights, in order to discuss the performances of each model and to assess the best location along the height of the structure. OpenSees is employed to calculate the high non-linearities of the models and to consider the interaction between the vertical loads and the horizontal forces. The various responses are discussed in terms of shear forces, accelerations and drifts, demonstrating the potentialities of inter-story isolation as a means of base isolation.